A comparative study of a front opening unified pod (FOUP) moisture removal efficiency with different purging gases. (November 2022) - Benalcazar, David; Lin, Tee; Hu, Ming-Hsuan; Zargar, Omid Ali; Lin, Shao-Yu; Shih, Yang-Cheng; Leggett, Graham
Abstract: Airborne molecular contamination (AMC) is one of the main causes of chip products defects during manufacturing. The downward moist air flow originated from the fan filter unit (FFU) inside the mini-environment (ME) can penetrate into the front opening unified pod (FOUP) and cause wafer defects. Purging nitrogen or clean dry air (CDA) are two common techniques used to minimize the relative humidity (RH) level inside the FOUP. This computational fluid dynamics (CFD) study compares purge performance of CDA and nitrogen when the FOUP door is open. The RH contours and moist air stream line were simulated inside the FOUP during purge. The FFU velocity, purging devices flow rate and temperature are kept constant during the simulation. An innovative large eddy simulation (LES) model was performed with the assistance of a small mesh size to simulate accurately the flow behavior inside the FOUP and ME. The results show that purging the FOUP with either CDA or nitrogen can significantly decrease the RH level to below 5% (RH < 5%). However, the FOUP purge with nitrogen is preferred due to the higher moisture removal efficiency. The CFD simulation results are verified by RH measurements with SHT-35 sensor inside the FOUP under the same processing conditions.